Scientific use of archival documets of Moscow Spiritual Consistory under the departmental restrictions of the Synodal period - Ilya Ivanov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article deals with a little-known and hardly imaginable in the context of pre-revolutionary clerical administration scientific direction of the Moscow Ecclesiastical Consistory Archive. Based on archival material and works of ecclesiastical Moscovites of the 19th - early 20th centuries the principles of the introduction of diocesan materials into science, as well as the parameters of departmental influence within the structures of church institutions on the example of the Moscow Ecclesiastical Consistory Archive are revealed. By the second quarter of the XIX century, the Consistory had acquired a large collection of diocesan documents with undisclosed information potential. Apart from departmental rules, the interest in the archive depended on psychological factors influencing research motivation. The establishment of science in the pre-revolutionary consistory archives was helped by a special committee which was set up in the first half of the 19th century to work with the archive complex. Its employees had to bear the main burden of searching for the necessary documents. The development of archives by the scientists was nonlinear: the periods of growth and decline alternated. Attention to the archive's documents was dulled by the change in OLDP's educational methodology, which replaced historical reconstructions with visual preaching. Nevertheless, the Archive's processing mechanisms were preserved and only the First World War interrupted further development of the information capacity of the Consistory archives. Thanks to the combined efforts of the clergy employed in the Archive, as well as the improved quality of the documents preserved, the Archive of the Diocesan Institution is gradually becoming a breeding ground for scholars studying the history of the Russian Church.